2015
DOI: 10.1021/acs.jproteome.5b00632
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Neuropeptidome Analysis Reveals Neuropeptides Are Correlated with Social Behavior Regulation of the Honeybee Workers

Abstract: Neuropeptides play vital roles in orchestrating neural communication and physiological modulation in organisms, acting as neurotransmitters, neuromodulators, and neurohormones. The highly evolved social structure of honeybees is a good system for understanding how neuropeptides regulate social behaviors; however, much knowledge on neuropeptidomic variation in the age-related division of labor remains unknown. An in-depth comparison of the brain neuropeptidomic dynamics over four time points of age-related poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 92 publications
0
70
0
Order By: Relevance
“…The pollen peptides were extracted at 4°C by the mixture solvent (methanol/H 2 O/acetic acid, 90:9:1, V/V/ V). After centrifugation at 16 099.2 g for 10 min, the supernatant was collected and vacuum-dried for further LC-MS/MS analysis and referred to the previously described method (Han et al, 2015).…”
Section: Peptidesmentioning
confidence: 99%
“…The pollen peptides were extracted at 4°C by the mixture solvent (methanol/H 2 O/acetic acid, 90:9:1, V/V/ V). After centrifugation at 16 099.2 g for 10 min, the supernatant was collected and vacuum-dried for further LC-MS/MS analysis and referred to the previously described method (Han et al, 2015).…”
Section: Peptidesmentioning
confidence: 99%
“…While this is no doubt a more accurate annotation, proteomics studies which utilize it still suffer from high rates of missed identifications relative to other model organisms. 17 Some recent honey bee proteomics publications that used modern instrumentation 18,19,20 have achieved identifications approaching the numbers reported in Chan et al (2013), 10 but have not exceeded them.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic selection of a high RJ-producing strain of bees (RJBs, A. m. ligustica ) from Italian bees (ITBs) has been conducted for nearly four decades in China since the 1980s. The RJBs can now produce 10 times greater amount of RJ than ITBs (Li et al 2007a, b;Li et al 2010;Feng et al 2015;Han et al 2015). Given the significantly elevated RJ outputs by RJBs, China is now the world's largest RJ producer and produces ∼ 3500 tons of RJ per year, which accounts for more than 90% of the world RJ market (Krell 1996;Cao et al 2016;Fratini et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although these markers are important for marker-based selection, knowledge on the molecular mechanism that drives the stronger performance of RJ production by RJBs is still required. To be noted, recent proteome researches have revealed that RJBs have reshaped the proteome setting of the HGs (Li et al 2010;Ji et al 2014), mandibular glands (MGs) (Huo et al 2016), hemolymph (Ararso et al 2018), and nervous system (Han et al 2015;Han et al 2017), to support their biological performance for the elevated RJ production, as compared to ITBs and other honeybee species and/or lines. In addition, proteome, phosphoproteome, and glycoproteome comparisons of RJ from RJBs and/or other honeybee species/lines have been carried out (Li et al 2007a, b;Chen and Li 2009;Fang et al 2010).…”
Section: Introductionmentioning
confidence: 99%